The Relation between Breadth and Depth of Vocabulary Knowledge and EFL Learner’s Speaking Performance - Kateryna Lizak; Лізак Катерина; Lizák Katalin (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2014)
Abstract. The present article is an attempt to highlight the sustained attention to the EFL learners' vocabulary knowledge and its development, as well as its relation to the development of speaking performance. It intends to determine whether breadth and depth of vocabulary knowledge are related to EFL learners' speaking performance, and to examine which one of these variables, that is, depth or breadth of vocabulary knowledge, makes a more important contribution to foreign language learners’ speaking performance. It also attempts to investigate whether there is a relationship between these two vocabulary knowledge dimensions. Finally, the study tries to determine whether there are any differences between ESL and EFL learners’ development of the vocabulary knowledge.

Резюме. Настоящая статья является попыткой указать на необходимость постоянного внимания к лексике и его развития изучающими английский язык как иностранный, а также его связи с развитием навыков говорения как средства формирования коммуникативной компетенции. Она намерена определить влияют ли количественный и качественный состав лексики на развитие навыков говорения, и которая из данных составных имеет более важный вклад на формирование коммуникативной компетенции. Статья также пытается исследовать, есть ли связь между этими двумя составными лексики. В исследовании сделана попытка определить, существуют ли какие-либо различия в процессе развития лексики английского языка между изучающими язык как иностранный и теми учащимися, для которых английский является вторым языком.
Взаимосвязь количественного и качественного состава лексики и развития навыков речи при изучении английского языка как иностранного
Keywords: vocabulary acquisition; vocabulary breadth; vocabulary depth; speaking performance